2011
DOI: 10.2139/ssrn.1805765
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Eco-innovations by Type of Environmental Impact: The Role of Regulatory Push/Pull, Technology Push and Market Pull

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
506
7
35

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(573 citation statements)
references
References 26 publications
25
506
7
35
Order By: Relevance
“…Horbach et al 2012). The main aim of this literature is to identify the specificities of eco-innovation, with respect to innovation tout court.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Horbach et al 2012). The main aim of this literature is to identify the specificities of eco-innovation, with respect to innovation tout court.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Del Río et al 2013;Ghisetti et al 2015) are thus particularly important and 'complement' investments made in organizational and technological capabilities (e.g. Horbach 2008; Demirel and Kesidou 2011;Horbach et al 2012). Embeddedness in (local) production systems and complementarity between different types of (eco-) innovation are also relevant emerging factors for the patterns of eco-innovation adoption by SMEs Zoboli 2005, 2009;Mazzanti et al 2008;Cainelli et al 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the compliance with the Lisbon agenda has been poor and although the Kyoto targets have been achieved, this was mainly due to the ongoing crisis (Borghesi 2011), and it is not clear whether the 20-20-20 targets will be achieved when the economy eventually recovers from the recession. Second, the link between environmental policy and eco-innovation is still at the center of economic debate which showed that the drivers of innovations in environmental technologies are multifaceted and touch upon various spheres of society and policy-making (Horbach et al 2012;Crespi 2008, 2013). Only properly designed policies can spur eco-innovations when firms believe that innovation offsets are greater than regulatory costs (Costantini and Mazzanti 2012).…”
Section: Introductionmentioning
confidence: 99%